2022
DOI: 10.3389/fneur.2022.888165
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the mechanisms of post-stroke motor recovery mediated by electroacupuncture using diffusion tensor tractography

Abstract: Acupuncture has been commonly used for post-stroke patients, and electroacupuncture allows simultaneous application of acupuncture and electrical stimulation. We aimed to elucidate the mechanism of electroacupuncture on post-stroke motor recovery using diffusion tensor tractography. A total of 33 subacute stroke patients were recruited. The control group was subjected to conventional rehabilitation therapy. In contrast, the patients in the experimental group received electroacupuncture treatment for 30 min per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The best treatment for FMA-LE and BBS were both included EA + BA+RT, which indirectly confirmed the effectiveness of this intervention, and also indicated that it may have the best effect in promoting the recovery of limb motor function and relieving spasticity. Studies have found that the use of EA in the acute stage of infarction can effectively improve the collateral circulation in the central area, increase cerebral blood perfusion, and reshape the brain motor function network ( 66 , 67 ). For the peripheral aspects, electroacupuncture can reduce the excitation threshold of nerve and muscle cells, increase the release of endogenous morphine peptides, so as to stimulate the antagonistic muscles of the affected limb, inhibit the muscle strength of the spastic muscles, and relieve the spasm of the limb ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The best treatment for FMA-LE and BBS were both included EA + BA+RT, which indirectly confirmed the effectiveness of this intervention, and also indicated that it may have the best effect in promoting the recovery of limb motor function and relieving spasticity. Studies have found that the use of EA in the acute stage of infarction can effectively improve the collateral circulation in the central area, increase cerebral blood perfusion, and reshape the brain motor function network ( 66 , 67 ). For the peripheral aspects, electroacupuncture can reduce the excitation threshold of nerve and muscle cells, increase the release of endogenous morphine peptides, so as to stimulate the antagonistic muscles of the affected limb, inhibit the muscle strength of the spastic muscles, and relieve the spasm of the limb ( 68 ).…”
Section: Discussionmentioning
confidence: 99%